HISTORY OF WOMEN'S FOOTBALL WORLD CHAMPIONSHIP IN 1991-2007 - Andrzej Soroka (Lesya Ukrainka Volyn National University, 2017)
The aim of this article was to show the initial stage of development of women's world football through the analysis of first five tournaments within the World Championships. Such beginning in the form of world class tournaments has allowed strengthening the position of women's football in the world, giving it international prestige. First tournament took place in China in 1991. Joao Havelange, a then FIFA president, was a great promoter of the establishment of the FIFA World Cup. The next world championships were played in Sweden. It was a perfect tournament in terms of organization. A turning point in women's football was a tournament played in 1999 in the United States. It was a great media success of women's football. This tournament broke the audience record of sport competitions involving women, as the final match was watched by more than 90 thousand spectators at the stadium. The next championships strengthened the position of football in the world. Currently, there is a need to monitor and register important events in women's football, as it happens in men's football.